Antibiotic‐induced dysbiosis of the microbiota impairs gut neuromuscular function in juvenile mice. (30th August 2017) - Caputi, Valentina; Marsilio, Ilaria; Filpa, Viviana; Cerantola, Silvia; Orso, Genny; Bistoletti, Michela; Paccagnella, Nicola; De Martin, Sara; Montopoli, Monica; Dall'Acqua, Stefano; Crema, Francesca; Di Gangi, Iole‐Maria; et al.
Abstract : Background and Purpose: Gut microbiota is essential for the development of the gastrointestinal system, including the enteric nervous system (ENS). Perturbations of gut microbiota in early life have the potential to alter neurodevelopment leading to functional bowel disorders later in life. We examined the hypothesis that gut dysbiosis impairs the structural and functional integrity of the ENS, leading to gut dysmotility in juvenile mice. Experimental Approach: To induce gut dysbiosis, broad‐spectrum antibiotics were administered by gavage to juvenile (3weeks old) male C57Bl/6 mice for 14 days. Bile acid composition in the intestinal lumen was analysed by liquid chromatography‐mass spectrometry. Changes in intestinal motility were evaluated by stool frequency, transit of a fluorescent‐labelled marker and isometric muscle responses of ileal full‐thickness preparations to receptor and non‐receptor‐mediated stimuli. Alterations in ENS integrity were assessed by immunohistochemistry and Western blot analysis. Key Results: Antibiotic treatment altered gastrointestinal transit, luminal bile acid metabolism and bowel architecture. Gut dysbiosis resulted in distorted glial network, loss of myenteric plexus neurons, altered cholinergic, tachykininergic and nitrergic neurotransmission associated with reduced number of nNOS neurons and different ileal distribution of the toll‐like receptor TLR2. Functional defects were partly reversed by activation of TLR2 signalling. Conclusions and Implications: Gut dysbiosis caused complex morpho‐functional neuromuscular rearrangements, characterized by structural defects of the ENS and increased tachykininergic neurotransmission. Altogether, our findings support the beneficial role of enteric microbiota for ENS homeostasis instrumental in ensuring proper gut neuromuscular function during critical stages of development.